2014
DOI: 10.1002/chem.201402151
|View full text |Cite
|
Sign up to set email alerts
|

Germanium Quantum Dots Embedded in N‐Doping Graphene Matrix with Sponge‐Like Architecture for Enhanced Performance in Lithium‐Ion Batteries

Abstract: Germanium quantum dots embedded in a nitrogen-doped graphene matrix with a sponge-like architecture (Ge/GN sponge) are prepared through a simple and scalable synthetic method, involving freeze drying to obtain the Ge(OH)4 /graphene oxide (GO) precursor and subsequent heat reduction treatment. Upon application as an anode for the lithium-ion battery (LIB), the Ge/GN sponge exhibits a high discharge capacity compared with previously reported N-doped graphene. The electrode with the as-synthesized Ge/GN sponge ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 64 publications
0
31
0
2
Order By: Relevance
“…Furthermore, the shift in the infrared spectra from 1,066 cm -1 , which corresponds to the C(3)-OH stretch [57] in chitin, to 1,071 cm -1 in the composite is well visible. Qin et al [58] reported that the formation of Ge-O-C bonds between germanium oxide and graphene oxide can be also indicated by the presence of a band at 1,380 cm -1 . However, in the case of this chitin-based composite, the absorbance at 1,378 cm -1 is assigned to CH bending and asymmetric deformation of CH 3 from chitin.…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, the shift in the infrared spectra from 1,066 cm -1 , which corresponds to the C(3)-OH stretch [57] in chitin, to 1,071 cm -1 in the composite is well visible. Qin et al [58] reported that the formation of Ge-O-C bonds between germanium oxide and graphene oxide can be also indicated by the presence of a band at 1,380 cm -1 . However, in the case of this chitin-based composite, the absorbance at 1,378 cm -1 is assigned to CH bending and asymmetric deformation of CH 3 from chitin.…”
Section: Resultsmentioning
confidence: 96%
“…Also the hybridized Ge/CNFs nanocomposite exhibited good Li storage performance, including high reversible capacity (1204 mA h g −1 at the current density of 200 mA g −1 ), high capacity retention (87.1% after 100 cycles), and rate property (760 mA h g −1 at 3000 mA g −1 ). Ge QDs embedded in an N‐doping GN matrix with a sponge‐like architecture (Ge/GN sponge) were prepared via freeze‐drying followed by a heat reduction process ( Figure a) . Figure b demonstrated that the Ge/GN sponge showed a good cycling stability, but it was not excellent; furthermore, the cycling stability could be advanced by developing a “double protection” method.…”
Section: Batteriesmentioning
confidence: 99%
“…Simultaneous carbon coating and the reduction of hollow ellipsoidal GeO 2 precursors facilitated the preparation of mesoporous and hollow ellipsoidal Ge encapsulated by a carbon source (Ge@C) that exhibited better cycling stability and higher rate capability than the solid analogue. In 2014, we also reported examples of embedding Ge NPs into an N‐doped porous carbon matrix (Figure ), such as a mesoporous Ge/N‐doped graphene (Ge/N‐GN sponge) and microporous Ge/N‐doped carbon nanofibers (Ge/N‐CNFs) . Compared with N‐GNs and N‐CNFs, an N‐doped mesoporous carbon matrix (CMK‐3)—a typical mesoporous carbon matrix—also acts as a rigid support and conductive framework, thereby providing good access to the electrolyte for fast charge transfer .…”
Section: Germaniummentioning
confidence: 99%
“… a) Schematic representation of the formation of a Ge/N‐GN sponge; b) TEM images of the Ge/N‐GN sponge; c) schematic representation of the formation of Ge/N−CNFs . EDA‐Ge‐PVP was obtained by dissolving GeO 2 in water‐ethanediamine (EDA) mixed solvent in the presence of polyvinylpyrrolidone (PVP).…”
Section: Germaniummentioning
confidence: 99%